Applied Nanotoxicology. (January 2016) - Hobson, David W.; Roberts, Stephen M.; Shvedova, Anna A.; Warheit, David B.; Hinkley, Georgia K.; Guy, Robin C.
Nanomaterials, including nanoparticles and nanoobjects, are being incorporated into everyday products at an increasing rate. These products include consumer products of interest to toxicologists such as pharmaceuticals, cosmetics, food, food packaging, household products, and so on. The manufacturing of products containing or utilizing nanomaterials in their composition may also present potential toxicologic concerns in the workplace. The molecular complexity and composition of these nanomaterials are ever increasing, and the means and methods being applied to characterize and perform useful toxicologic assessments are rapidly advancing. This article includes presentations by experienced toxicologists in the nanotoxicology community who are focused on the applied aspect of the discipline toward supporting state of the art toxicologic assessments for food products and packaging, pharmaceuticals and medical devices, inhaled nanoparticle and gastrointestinal exposures, and addressing occupational safety and health issues and concerns. This symposium overview article summarizes 5 talks that were presented at the 35th Annual meeting of the American College of Toxicology on the subject of "Applied Nanotechnology."